วาทะในการอภิปรายไม่ไว้วางใจรัฐบาล ของนายชวน หลีกภัย กรณีส.ป.ก.4-01 - พรทิพย์ เอื้ออุฬาร (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Analyses rhetoric of no-confidence debate of Chuen Leekpai s government on the issue of agricultural land reform office 4-01. All annual meeting minutes of May 17-19, B.E. 2538 and also newspaper news were gathered, by setting up 2 analysis-leading problems, as follows:- 1. How is the rhetoric situation of no-confidence debate of Chuen Leekpai s government on the issue of agricultural land reform office 4-01? 2. The nature of the outline of reasoning on rhetoric of no-confidence debate of Chuen Leekpai s government on the issue of agricultural land reform office 4-01? The research outcome as detailed as follows:- 1. Exigence in seeking for the opening of no-confidence debate of Chuen Leekpai s government on the issue of agricultural land reform office 4-01, was caused by the newspaper disclosure of transferring the land ownership to the rich by the ruling government. This news created a series of protest to various groups of people, assemblies for requesting for their duly rights. These protests led to a no-confidence debate petition of the opposition to verify the administration of the government and force the government to publicly inform people on what had happened. 2. Audience : there were two groups of audience, those were the government members of parliament, opposition members of parliament and people of all professions. 3. Constraints : Before the no-confidence debate held, there were some constraints which had been caused by the lack of public belief and the conflict among the members of government themselves. 4. Speaker : Both opposition and government speakers addressed reasons and presented information to support to their discussion. 5. Speech : Rhetoric analysis by using the Stephen Toulmin s structures, found that the opposition presentation in giving reasoning to support their debates were groundless, for example; illegal violation of the land reform act without citing the appropriate land law, which act of law or what were the essential matters to be referred to, while the government side, mentioned to the poor in Phuket but there were no any evidences to confirm the citizens of Phuket are really in such condition. Most of the evidences produced in the debate were the law provisions taken to defeat the opposition, just for creating public belief on what the government had done agreeable with the constitution.